Mathematics Teachers' Competency Development: A Qualitative Study On The Transition From PMM To Ruang GTK - Fadhil Zil Ikram; Yaya Sukjaya Kusumah; Mei Radia Putri (Information Technology Education Journal, 2025)
The change from PMM (Merdeka Mengajar Platform) to Ruang GTK requires further study investigating how the Ruang GTK is utilised compared to PMM. The present qualitative study aims to describe the experiences of 15 mathematics teachers (13 teachers and two vice principals) in using Ruang GTK compared to their previous experiences using PMM. The study spanned six weeks and was conducted online and offline. The data were collected through interviews and audiovisual materials, with interview guidelines developed based on an adaptation of the Technology Acceptance Model (TAM3) constructs: perceived usefulness, perceived ease of use, job relevance, voluntariness, and use. The data underwent a three-stage analysis process, encompassing data condensation, data presentation, verification, and conclusion drawing. The results showed that more and more participants rarely use Ruang GTK due to motivational factors, changes in the curriculum, and the need to attend many offline trainings. The discrepancy in the advantages accruing from utilizing Ruang GTK compared to PMM can be attributed to the substantial diminution in teacher workload. Ruang GTK is easier to operate, especially because it eliminates features that confuse teachers. Lastly, many of the participants now access the Ruang GTK only when there is an obligation or demand from their superiors, and only a few